(3KHJ Hef dbjge GdJGhOi HeUQ hGdMQejfs - (3eMeO GdJGhOj Hf eMeO GdWGdH Hf eMeO Hf Ydj GHf ShOg GdeQj,J (B1209 (3g` s
(3ChdgG (B:s
(3hbO QCjJ CPcQ Ydi LgI GdGNJUGQ LedI eGdbjJg HGdOjGQ GdeUQjI s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hBNQkG hUdi Gddg Ydi Cced GdYGdejf hGdSdGe ef cGJHg CMeO Hf YHO Gdddg GdQHGWi eTJFkG GdOcGdi CUdoG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B342 - (3U(B360s
(3ZjQ ehLhO HGdYdHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B62 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B125s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B689 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B136 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(285 (3O(B) s
Keywords: (3GdJGQjNs